I'm not sure where to start on this one. It has me tricked. here it is: (X-2)(X-3) + (X-2) Thanks for your help
Follow Math Help Forum on Facebook and Google+
Originally Posted by MathMack I'm not sure where to start on this one. It has me tricked. here it is: (X-2)(X-3) + (X-2) Thanks for your help (X-2)(X-3) + (X-2) = (X-2)(X-3) + 1 (X-2). Now take out the common factor of (X - 2).
What's the reasoning to adding the 1? Thank you so much for your help
Originally Posted by MathMack What's the reasoning to adding the 1? Thank you so much for your help To help you see how to factorise the expression when you attempt to take out the common factor.
Originally Posted by MathMack What's the reasoning to adding the 1? Thank you so much for your help He is using the "distributive law": ab+ ac= a(b+ c). In (X-2)(X-3) + (X-2), a= (X-2), b= (X-3), and c= 1: (X-2)(X-3)+ (X-2)(1)= (X-2)((X-3)+ (1))= (X-2)(X-2)
View Tag Cloud